CRESCIMENTO DE MUDAS DE BARU EM DIFERENTES SOMBREAMENTOS E SUBSTRATOS - COSTA, Renato Morais; COSTA, Edilson; SOUZA, Jéssica Andrade Diniz; MARTINS, Vinícius da Silva Freitas; SANTOS, Renan Marcelo Ferreira dos (ANAIS DO ENIC, 2017)
-